ANALISIS HUBUNGAN KORUPSI,DEMOKRASI DAN PERTUMBUHAN EKONOMI DI INDONESIA - Putri, Lucia Maison; Triani, Mike (Universitas Negeri Padang, 2020)
Abstract: The study was conducted to: (1) Determine the response to corruption resulting fromthe shock of democracy and economic growth in Indonesia. (2) Knowing the democratic responseresulting from the shock of corruption and economic growth in Indonesia. (3) Knowing theresponse to economic growth due to the shock of corruption and democracy in Indonesia. Thistype of research is descriptive using a quantitative approach. The data used in this study aresecondary data, sourced from the KPK annual report website and sourced from BPS (BadanStatistics Center). VAR analysis method is used to determine the two-way relationship betweenvariables.The results of the research are: (1) There is no causal relationship between corruption anddemocracy. However, there is only a one-way relationship between corruption and democracy (2)There is no causal relationship between corruption and economic growth. However, there is onlya one-way relationship between corruption and growth. economy (3) There is no causalrelationship between democracy and economic growth. However, there is only a one-wayrelationship between democracy and economic growth.Based on the research results, it is suggested that the Government can implement policies inhandling cases of corruption and democracy because it will affect the welfare of society and thegovernment system in Indonesia. The government also pays more attention to the public sectorand the community's economic sector so that they can contribute to improving the welfare of thecommunity. This is aimed at improving the welfare of the Indonesian people.Keywords: Corruption, Democracy, Economic Growth, VAR.